Pengaruh strategi penilaian K-13 terhadap motivasi dan hasil belajar IPS-Geografi siswa di SMP Nasional dan SMP Budi Mulia Pakisaji - Yuli Ifana Sari; Dwi Kurniawati (Jurnal Teori dan Praksis Pembelajaran IPS, 2016)
Authentic assessment focuses on three aspects of the assessment that is affective, cognitive and psychomotor. Authentic assessment system contained in the curriculum in 2013 were appropriate and were able to increase the result and motivation to learn. With the implementation good curriculum will either produce output learning results good also. The purpose of this research is to analize and know: 1) Significant influence of K13 assessment strategies to student learning motivation. 2) Significant influence of K13 assessment strategies to student learning outcomes. This research  is causal. The population in this study were all students of Class VIII SMP and SMP Budi Mulia National Pakisaji academic year 2015/2016, amounting to 268 students. Proportional random sampling, the samples taken 30% of the 268 students are 86 students. The research instrument using a questionnaire, to obtain good data and correct, the use of the instrument should be tested first. Data collection techniques used in this study is: (1) technical questionnaires and (2) technical documentation. Testing the hypothesis in this study using a t-test. Adapun significance level used is 5%. Calculation of data analysis using SPSS. The results of t test analysis showed that the K-13 assessment strategies did not affect significantly to the motivation and learning outcomes.Keyword: Motivation, learning outcomes, and assessment of K-13. http://dx.doi.org/10.17977/um022v1i22016p116